Electrocatalytic reduction of CO2 by thiophene-substituted rhenium(i) complexes and by their polymerized films. Issue 37 (22nd January 2016) - Sun, Cunfa; Prosperini, Simona; Quagliotto, Pierluigi; Viscardi, Guido; Yoon, Sam S.; Gobetto, Roberto; Nervi, Carlo
Abstract : Three novel Re complexes with thiophene substituted bipyridine ligands were electropolymerized on GCE surface by oxidation. The surface-modified electrodes were tested for electrocatalytic CO2 reduction. Abstract : Three novel thiophene substituted bipyridine ligands and their corresponding rhenium complexes were synthesized and tested for the electrocatalytic reduction of CO2 . Two complexes underwent oxidative electropolymerization on a glassy carbon electrode (GCE) surface. The conductive polymers chemically deposited on the GCE allow electron transport from the surface to the polymer-attached rhenium catalytic center in contact with the solution. The chemically modified electrodes show significant catalytic activities for CO2 reduction, and moderate relative higher stabilities when compared with the homogeneous solution counterparts.